Classement de métonymies et traduction automatique - Czekaj, Anna (Neophilologica, 2020)
The paper is a continuation of the author’s previous work regarding the legitimacy of metonymy classification for the needs of automatic translation. The author attempts to solve the problem presented in the paper entitled Classification of metonymy and its usefulness in automatic translation and proposes her classification of metonymic expressions, which could be a helpful tool in computer translation.